American economic review - American Economic Association (Nashville, TN American Economic Association, 1958)
The American Economic Review is a general-interest economics journal. Established in 1911, the AER is among the nation's oldest and most respected scholarly journals in the economics profession and is celebrating over 100 years of publishing! The journal publishes 11 issues containing articles on a broad range of topics as well as the Papers and Proceedings issue in May, which presents selected papers from the AEA's annual meeting along with the reports of officers and committees
The library has vol. 55 to 73 (1965-1983) as a gift from BZU From 2006-2010 missing incomplete sets: 2010 - 2015 Frequency varies: 1999-2010 (5 issues), 2011-2013 (7 issues), 2013- (12 issues)
Keywords: Economics; ECONOMICS; PERIODICALS